Volatile metabolomics analysis reveals the flavor response of different parts of celery to ultraviolet radiation - Zhengnan Yan; Zhixin Li; Haokai Wang; Haijie Dou; Jinxiu Song; Fang Ji; Yanjie Yang; Duo Lin (Food Chemistry: X)
Volatile metabolomics was used to analyze volatile organic compounds in celery (Apium graveolens L. cv. Dayehuang) leaves and petioles under ultraviolet (UV) radiation. Results indicated that celery encompassed 328 terpenes, 299 esters, 178 heterocyclic compounds, and 166 ketones. The additional UV radiation altered ester and heterocyclic compound in celery leaves and changed terpenoids, aldehyde, and ester in celery petiole. The content of volatile organic compounds in leaves and petiole of celery under UV radiation was significantly higher than that grown without UV radiation. The content of 40 compounds with green, floral, woody, sweet, citrus, and fruity aromas have significantly altered in celery petioles. In addition, 24 compounds were significantly altered in celery leaves, including woody and sweet. Our study provides a valuable insight into the influences of UV radiation on different parts of celery flavor, and offers a possible way to alter the flavor quality of celery.